Birthright : a black roots music compendium [compact disc]. - Harris, Corey; Thomas, Shardé; McDowell, Fred; Baker, Etta, 1913-2006; Bois-sec; Fontenot, Canray; Hopkins, Lightnin', 1912-1982; Richardson, Benny; McGhee, Brownie, 1915-1996; Terry, Sonny; Roberts, Dink, 1894-1989; Burnside, Cedric; et al. (Craft Recordings, 2022)
In the span of just 40 songs, Birthright offers an expansive overview of American Black roots music ? from old-time banjo and traditional jazz to Mississippi hill country blues ? demonstrating the pervasive influence of these styles on popular culture from country to hip hop. This rollicking ride through the joyful landscape of African American musical invention includes essays from musician/scholars Dom Flemons and Corey Harris.